Relative Effectiveness of Extension Teaching Methods in retention of knowledge by Farm Women - T.S. Riar; Rajinder Peshin (Journal of Agricultural Extension Management, 2025)
Research institutes and other organizations engaged in agricultural research give out many ideas, new technologies and innovations of interest to the farming community. An innovation may be a new variety of a crop, breed of animal/ poultry, a new implement or a method to prepare a processed product. These technologies cannot be locked within the four walls of the laboratories, where they originated. They need to be transferred to the ultimate users of the technology, i.e. farmers or homemakers. However there is a wide gap between technology development, dissemination and adoption (Khanna, 1977